2018
DOI: 10.1016/j.clineuro.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of TNF-α, but not other pro-inflammatory cytokines, single nucleotide polymorphisms with intervertebral disc degeneration in Iranian population

Abstract: Polymorphisms of pro-inflammatory cytokine genes could take part in IVDD pathophysiology as the result of alteration in their expression levels or structures. The current study indicated significant roles of TNF-α -308 G/A and TNF-α -238 G/A SNPs with IVDD among Iranian patients. However, this study did not show any significant association between IVDD and either of SNPs of IL-1 and IL-6 genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…In the degenerative disc tissue samples, lots of inflammatory cytokines including TNF-α, IL-1β, and IL-17 are found to be increased [ 6–9 ]. Previously, inflammation cytokines were proved to play an important role in regulating disc cell biology and disc matrix metabolism [ 10–13 ]. Importantly, several studies have demonstrated that inflammation cytokines can promote disc cell death [ 14–16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the degenerative disc tissue samples, lots of inflammatory cytokines including TNF-α, IL-1β, and IL-17 are found to be increased [ 6–9 ]. Previously, inflammation cytokines were proved to play an important role in regulating disc cell biology and disc matrix metabolism [ 10–13 ]. Importantly, several studies have demonstrated that inflammation cytokines can promote disc cell death [ 14–16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may lead to inflate the chance of a false positive association. More importantly, three genetic studies focusing on this topic were published in recent years [23][24][25], which were not included in Wang's study. Based on the Cochrane guidelines[30], an overlapping meta-analysis is necessary to be updated in time with latest studies.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to in ate the chance of a false positive association. More importantly, three genetic studies focusing on this topic were published in recent years [23][24][25], which were not included in Wang's study. Based on the Cochrane guidelines [30], an overlapping meta-analysis is necessary to be updated in time with latest studies.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely studied of these are IL-1α rs1800587, IL-1β rs1143634 polymorphisms and variable number tandem repeat polymorphism (VNTR) of the IL-1RN gene. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] In 2004, Solovieva et al rst reported that IL-1α rs1800587 and IL-1β rs1143634 polymorphisms were associated with LDD risk in a Caucasian population [11]. The association of the IL-1α rs1800587 polymorphism to LDD was subsequently con rmed in Finnish and Danish population studies [15,16].…”
Section: Introductionmentioning
confidence: 99%